Analysis of 100 sputum positive pulmonary tuberculosis patients: a retrospective study - Srinivas, H. D. (International Journal of Research in Medical Sciences, 2024)
Background: The bacterium Mycobacterium tuberculosis causes tuberculosis (TB), a contagious, airborne infection that destroys body tissue. Pulmonary TB occurs when M. tuberculosis primarily attacks the lungs. However, it can spread from there to other organs. Pulmonary TB is curable with an early diagnosis and antibiotic treatment. Methods: The present study was conducted at Adichunchanagiri Institute of Medical Sciences, Mandya with total of 100 sputum positive TB cases. The analysis was done between January 2023 to June 2023. Results: The proportion of sputum positive pulmonary tuberculosis and sputum positivity was highest in 20 to 40 years age group. The number of sputum positive pulmonary tuberculosis was three times more common in male compares to female. Conclusions: The highest burden of sputum positive pulmonary tuberculosis and maximum sputum positivity rate was found in productive age group. The proportion of sputum positive PTB was more in male than female patients. All age group except in patient between 0-19 year’s ratio between male and female were almost equal.